Differences in kidney-specific DPP-4 inhibition by linagliptin and sitagliptin. (September 2018) - Luippold, Gerd; Mark, Michael; Klein, Thomas; Amann, Kerstin; Daniel, Christoph
Abstract: The two dipeptidyl peptidase (DPP)-4 inhibitors, linagliptin and sitagliptin, were shown to exert different binding kinetics in vitro . Twenty-four hours after oral dosing particularly in vivo inhibition of renal-specific DPP-4 activity was more sustained in Sprague Dawley rats after exposure to linagliptin than it was after sitagliptin.